Evaluation of Genotype, Environment, and Management Interactions on Fava Beans under Mediterranean Field Conditions - Mohamed Houssemeddine Sellami; Antonella Lavini; Davide Calandrelli; Giuseppe De Mastro; Cataldo Pulvento (Agronomy, 2021)
Faba beans (Vicia faba L.), also known as fava beans, like other crops, are influenced by several factors: their genotype, environment, and management, as well as the interaction between these, have an important impact on seed yielding and seed quality traits. This study was conducted at three locations in South Italy between 2017 and 2019 to evaluate the sowing date effect on yield and yield components of three Vicia faba L., originating from cool climates. The results showed that seed yield (SY) and yield components declined with sowing delay. The crop’s environment (year × site) and management (sowing date) were found to explain 34.01% and 42.95% of the total seed yield variation, respectively. The data showed that the tested genotypes were positively influenced by the environment with sandy loam soil and early winter sowing date, resulting in either a greater number of SY and THS than in the other environment. The three faba bean genotypes showed tolerance to winter frost conditions in the two growing seasons.